Karl Marx’s Eco-Socialism and Vision of Post-Capitalist Society - Edy Syahputra Sihombing; Jh Fandi Gilar Saputro; Yusuf Siswantara (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2026)
Environmental degradation and climate change are serious global issues that threaten human life both today and in the future. In response to these crises, Kohei Saito seeks to investigate the idea of Marx’s eco socialism as a potential alternative. Marx’s ecological thinking is rooted in a critique of the capitalist mode of production, as the fundamental cause of environmental destruction. His criticism of capitalism centers on the idea of a